Tools and Techniques: Self-Potential Methods - Jackson,MD (2015)
The self-potential (or spontaneous potential) (SP) method comprises the passive measurement of electric potential at the ground surface and in boreholes. SP methods have a number of advantages over other geophysical techniques: They are often cheaper and quicker to implement, requiring only a pair (or more) of suitable electrodes and a high-impedance voltmeter, and data can be obtained over large regions with dense sampling in both space and time. Moreover, SP anomalies are often directly related to the process of interest, such as changes in groundwater flow, chemistry, and/or temperature. The disadvantages largely lie in interpreting the data, which can be more challenging than other geophysical techniques. Similar to gravity and magnetic methods, SP measurements are purely passive, so there is often no way of adjusting source parameters to help identify signals of interest. Moreover, SP signals arise from a variety of sources, and distinguishing these can be challenging. Traditional SP surveys for mineral exploration, and borehole SP logs, have been interpreted qualitatively or semiquantitatively; however, a new generation of inversion techniques for SP measurements are now becoming available, driven by improved understanding of the underlying physical processes and increased computing power. Furthermore, the range and number of applications of the SP methods have rapidly increased in recent years.